High temperature resistant plugging anti-sloughing drilling fluid treatment agent and preparation method thereof
Patent Information
- Application Number
- CN202611382000.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-23
AI Technical Summary
常规聚合物类处理剂能够通过吸附、增黏和成膜作用改善滤饼质量,并在一定程度上抑制黏土颗粒分散,但其在高温、高盐和强剪切条件下稳定性不足,容易出现热降解和分子构象收缩,导致处理效果下降
(1)本发明通过2-丙烯酰胺基-2-甲基丙磺酸、丙烯酸、丙烯酰胺、N-乙烯基吡咯烷酮、二甲基二烯丙基氯化铵、甲基烯丙基聚氧乙烯醚和N,N'-亚甲基双丙烯酰胺形成复合聚合物网络,使抗高温封堵防塌型钻井液处理剂兼具耐盐水化、吸附分散、包被增黏、阳离子抑制和轻度交联增强作用。该聚合物网络在高温盐水环境下能够保持较好的链段伸展状态和水化膜稳定性,减少热降解和盐析收缩对处理剂性能的影响,从而提高钻井液的流变保持能力、滤失控制能力和岩屑包被能力。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of drilling fluid treatment agent technology, specifically relating to a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent and its preparation method. Background Technology
[0002] With the ongoing development of deep oil and gas resources, complex structural oil and gas reservoirs, and unconventional oil and gas resources, the formation conditions encountered during drilling are becoming increasingly complex. Problems such as rising bottomhole temperatures, increased formation pressure, enhanced hydration sensitivity of shale and mudstone, and the development of microfractures and nanopores are becoming more prominent. Water-based drilling fluids are widely used due to their environmental friendliness, low cost, and ease of on-site maintenance. However, under high-temperature environments, conventional water-based drilling fluid treatment agents are prone to molecular chain breakage, adsorption layer desorption, viscosity decay, and reduced filtration control capabilities. This leads to a large influx of drilling fluid filtrate into the formation, causing hydration expansion, dispersion and spalling of the wellbore rock, and a decrease in mechanical strength. This, in turn, can induce complex downhole accidents such as borehole narrowing, blockage, stuck pipe, lost circulation, and wellbore collapse. Therefore, developing drilling fluid treatment agents that combine high-temperature resistance, plugging, and collapse prevention functions is a key technological direction for improving drilling safety and wellbore stability in complex formations.
[0003] Existing drilling fluid treatment agents typically include filtration loss reducers, coating agents, shale inhibitors, and plugging agents. Conventional polymer-based treatment agents can improve filter cake quality through adsorption, thickening, and film formation, and to some extent inhibit clay particle dispersion. However, they lack stability under high temperature, high salinity, and strong shear conditions, and are prone to thermal degradation and molecular conformational shrinkage, leading to a decrease in treatment effectiveness. Inorganic particulate plugging materials can enter formation pore throats or microfractures to form a physical plugging layer by matching particle size. However, single inorganic particles are prone to agglomeration and sedimentation, have poor compatibility with polymer systems, and are difficult to form a continuous, tough, and dense composite plugging film on the wellbore surface. Traditional large-particle plugging agents are mainly suitable for larger fractures or pores, and are insufficient for plugging the micro-nano pores widely present in shale. Although single nanomaterials can improve the plugging effect of fine pores, they lack dispersion stability in complex electrolyte environments and lack effective bonding with the wellbore surface and polymer network. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent and its preparation method.
[0005] In a first aspect, the present invention provides a method for preparing a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, comprising the following steps: S1. By weight, mix 120.0-190.0 parts deionized water, 18.0-32.0 parts 2-acrylamido-2-methylpropanesulfonic acid, and 4.0-10.0 parts acrylic acid, and adjust the pH to 6.8-7.2 with sodium hydroxide to obtain a neutralized monomer solution; add 28.0-45.0 parts acrylamide, 6.0-15.0 parts N-vinylpyrrolidone, 5.0-13.0 parts dimethyl diallyl ammonium chloride, 2.0-6.0 parts methyl allyl polyoxyethylene ether, and 0.04-0. 18 parts of N,N'-methylenebisacrylamide were mixed to obtain a composite monomer solution. 1.5-5.0 parts of vinyltrimethoxysilane were added to a mixture of 8.0-18.0 parts of anhydrous ethanol and 8.0-15.0 parts of deionized water. The pH was adjusted to 4.0-5.0 with glacial acetic acid, and hydrolysis was performed to obtain a silane hydrolysate. The silane hydrolysate was added to the composite monomer solution, along with 4.0-10.0 parts of titanium-silicon-aluminum intercalated vermiculite nanosheets and 1.5-5.0 parts of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres. The mixture was ultrasonically dispersed to obtain an inorganic composite monomer dispersion.
[0006] S2. Under a nitrogen atmosphere, heat the inorganic composite monomer dispersion to 45-55℃, add 0.15-0.45 parts of ammonium persulfate and 0.15-0.45 parts of sodium bisulfite to react and obtain a polymer gel; cut the polymer gel into small pieces, vacuum dry, pulverize and sieve.
[0007] In this invention, the formation of a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent is based on the core processes of water-soluble monomer free radical polymerization and inorganic particle composite fixation. In deionized water, 2-acrylamido-2-methylpropanesulfonic acid and acrylic acid are neutralized with sodium hydroxide to form a neutralized monomer solution with sulfonate and carboxylate groups. The sulfonate groups have strong hydration ability and are not sensitive to temperature, while the carboxylate groups provide additional charge density. Together, they are beneficial to improving the hydration stability and dispersion stability of the polymer under brine and high-temperature conditions. Acrylamide provides amide groups and flexible backbone segments to contribute to solution thickening capacity. The rigid five-membered lactam ring structure in N-vinylpyrrolidone improves the temperature resistance of the chain segments and enhances high-temperature hydrolysis resistance. Dimethyl diallyl ammonium chloride undergoes intramolecular cyclization polymerization under free radical conditions and provides cationic adsorption sites to enhance the adsorption and coating effect on negatively charged wellbore shale. Methyl allyl polyoxyethylene ether provides steric hindrance and hydration protection layer with its long polyether chain. N,N'-methylenebisacrylamide forms mild covalent crosslinking points between molecular chains, giving the polymer network moderate strength without excessive crosslinking. In an acidic medium composed of anhydrous ethanol, deionized water, and glacial acetic acid, vinyltrimethoxysilane undergoes stepwise hydrolysis of the methoxy group to form a silane hydrolysate containing silanol groups. Upon addition to the composite monomer solution, the silanol groups can participate in organic chain linking within the polymerization system and condense with the hydroxyl groups on the surface of silicon spheres sealed by titanium-silicon-aluminum intercalated vermiculite nanosheets and phosphotungsten-cerium-zirconium oxygen clusters, thus establishing a chemical bridge between the inorganic components and organic chains. Ammonium persulfate and sodium bisulfite undergo a redox reaction under a nitrogen atmosphere to generate sulfate radicals. These sulfate radicals attack the vinyl double bonds of each monomer, initiating chain growth reactions and immobilizing the two inorganic modified components within the polymer's three-dimensional network through encapsulation, entanglement, and surface condensation bonding. This results in an organic-inorganic composite polymer gel with coating adsorption, temperature and salt resistance, sheet-like bridging and sealing, and spherical gap-filling sealing properties. After shearing, vacuum drying, pulverizing, and sieving, a high-temperature resistant, anti-collapse drilling fluid treatment agent with good dispersibility and application stability is obtained.
[0008] According to a preferred embodiment of the present invention, in step S1, the hydrolysis time is 20-40 min; the ultrasonic dispersion time is 20-40 min.
[0009] According to a preferred embodiment of the present invention, in step S2, the reaction time is 5-8 hours; and the vacuum drying temperature is 70-85°C.
[0010] According to a preferred embodiment of the present invention, the method for preparing the titanium-silicon-aluminum intercalated vermiculite nanosheets includes: A1. By weight, add 20.0-30.0 parts of expanded vermiculite powder to 180.0-260.0 parts of a 1.0 mol / L hydrochloric acid aqueous solution, stir at 65-75℃, filter, wash, and dry to obtain acidified vermiculite; add the acidified vermiculite to 220.0-300.0 parts of deionized water, add 2.0-5.0 parts of sodium hexametaphosphate, disperse, then add a mixture containing 8.0-14.0 parts of tetraisopropyl titanate, 6.0-10.0 parts of acetylacetone and 40.0-70.0 parts of anhydrous ethanol, stir at 25-30℃, then add 5.0-9.0 parts of tetraethyl orthosilicate and 4.0-8.0 parts of aluminum nitrate nonahydrate, add ammonia to adjust the pH to 8.5-9.2, stir at 45-55℃ to obtain a titanium-silicon-aluminum intercalated vermiculite suspension.
[0011] A2. The titanium-silicon-aluminum intercalated vermiculite suspension is transferred into a reactor and hydrothermally treated at 150-170℃. After cooling, centrifugation, washing, and drying, the hydrothermally treated product is obtained. The hydrothermally treated product is calcined at 350-420℃, ground, and sieved.
[0012] In this invention, the formation of titanium-silicon-aluminum intercalated vermiculite nanosheets primarily relies on the acidification and activation of expanded vermiculite powder. After treatment with hydrochloric acid aqueous solution using the 2-acrylamido-2-methylpropanesulfonic acid system, the exchangeable cations between the layers of the expanded vermiculite powder are partially replaced, and some magnesium and iron cations in the octahedral sheets are dissolved. This exposes more silanol and aluminum hydroxyl sites at the sheet edges and between layers, making them more readily adsorbed, complexed, and deposited with subsequent inorganic precursors. After the acidified vermiculite is dispersed in deionized water, sodium hexametaphosphate exerts a dispersing and electrostatic stabilizing effect by adsorbing onto the sheet ends and imparting a negative charge, weakening the van der Waals forces between the sheets and maintaining the acidified vermiculite in a good suspended state, thus providing conditions for the uniform deposition of subsequent inorganic species. Tetraisopropyl titanate undergoes complexation with acetylacetone in anhydrous ethanol, resulting in partial chelation and substitution of the isopropoxy group to form a stable intermediate coordinated with acetylacetone. This significantly slows down the hydrolysis rate, preventing the rapid formation of large titanium oxide precipitates upon direct contact with water. Upon addition of acidified vermiculite dispersion to this complexation system, titanium species gradually hydrolyze and deposit on the surface and between vermiculite layers. Tetraisopropyl orthosilicate simultaneously undergoes hydrolysis and condensation to form a silicon-oxygen network structure. Aluminum nitrate nonahydrate, under ammonia-regulated conditions, undergoes hydrolysis to form aluminum hydroxyl species and aluminum hydroxide colloids. Titanium species, the silicon-oxygen network structure, and the aluminum hydroxyl species are co-adsorbed and deposited on the surface and between layers of acidified vermiculite, and through dehydration condensation between hydroxyl groups, form titanium-oxysilicon, titanium-oxyaluminum, and mixed silicon-oxyaluminum bonded structures. After hydrothermal treatment, the amorphous precursors in the system further condense and rearrange, transforming into quasi-crystalline titanium-silicon-aluminum composite oxides, while forming a stronger chemical bond with vermiculite sheets. Subsequently, calcination at a higher temperature removes residual organic groups and solidifies the titanium-silicon-aluminum composite oxide structure, thereby obtaining titanium-silicon-aluminum intercalated vermiculite nanosheets with sheet support, interlayer intercalation, and surface inorganic oxide modification. This structure combines high specific surface area, good interlayer channels, and high-temperature stability.
[0013] According to a preferred embodiment of the present invention, in A1, the stirring time at 45-55°C is 2-4 hours.
[0014] According to a preferred embodiment of the present invention, in A2, the hydrothermal treatment time at 150-170°C is 8-12 hours; and the calcination time at 350-420°C is 2-4 hours.
[0015] According to a preferred embodiment of the present invention, the method for preparing the phosphotungsten-cerium-zirconium-oxygen cluster-sealed silicon sphere includes: B1. By weight, add 6.0-10.0 parts of tetraethyl orthosilicate to 80.0-120.0 parts of anhydrous ethanol, add 20.0-35.0 parts of deionized water and 3.0-6.0 parts of ammonia, stir at 25-30℃, centrifuge, and wash to obtain a wet nano-silica gel; disperse the wet nano-silica gel in 150.0-220.0 parts of deionized water, add 1.5-3.5 parts of cerium nitrate hexahydrate, 1.0-2.5 parts of zirconium oxychloride octahydrate and 2.5-5.5 parts of phosphotungstic acid hydrate, stir at 45-55℃, adjust the pH to 1.0-1.8 with nitric acid, then add 0.5-1.2 parts of acidic silica sol, age at 80-90℃ to obtain a suspension of phosphotungstic cerium zirconium oxide cluster-blocking silica spheres.
[0016] B2. Filter, wash, and dry the suspension of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres to obtain a dried product; calcine the dried product at 280-340℃, grind, and sieve.
[0017] In this invention, the formation of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres is based on the hydrolytic condensation of tetraethyl orthosilicate. In an alkaline medium composed of anhydrous ethanol, deionized water, and ammonia, the ethoxy groups in tetraethyl orthosilicate are gradually replaced by hydroxyl groups to generate silanol intermediates. These silanols then continue to condense to form a uniform nano-silica wet gel. The resulting wet gel exhibits an approximately spherical particle morphology with a large number of incompletely condensed silanol groups on its surface, providing abundant binding sites for subsequent loading of cerium nitrate hexahydrate, zirconium oxychloride octahydrate, and phosphotungstic acid hydrate. After the nano-silica wet gel is redispersed in deionized water, cerium nitrate hexahydrate ionizes in water to release trivalent cerium ions, and zirconium oxychloride octahydrate hydrolyzes to release zirconium oxide cations. Both further undergo hydration and combine to form cerium and zirconium species with hydroxyl groups. Some of these cerium and zirconium species form polynuclear hydroxyl complexes through oligomerization. The phosphotungstic acid hydrate ionizes in water to provide phosphotungsten heteropoly anions with a cage-like structure, maintaining their intact structure without disintegration under acidic conditions. After adjusting the pH to a suitable range with nitric acid, positively charged cerium and zirconium species and negatively charged phosphotungsten heteropoly anions form cerium-zirconium-phosphotungsten composite oxygen clusters through electrostatic adsorption and coordination. These clusters are simultaneously anchored to the silanol groups on the surface of the nano-silica wet gel via deposition. Acidic silica sol is then added, and during aging, it undergoes further hydrolysis and condensation to form a silicon-oxygen network, creating a denser and more stable inorganic bonding layer between the cerium-zirconium species, the phosphotungsten heteropoly anion structure, and the silicon sphere surface, filling the micropores in the oxygen cluster deposition layer. After filtration, washing, and drying, free water, residual solvent, and some weakly bound components are removed from the system. Subsequent calcination at a lower temperature preserves the phosphotungsten heteropoly anion structure, while the cerium and zirconium species are further converted into cerium- and zirconium-containing oxides. This ultimately forms a composite oxygen cluster sealing layer containing phosphorus, tungsten, cerium, and zirconium elements on the silicon sphere surface, resulting in phosphotungsten-cerium-zirconium oxygen cluster-sealed silicon spheres.
[0018] According to a preferred embodiment of the present invention, in B1, the stirring time at 45-55°C is 1-2 hours; and the aging time at 80-90°C is 4-6 hours.
[0019] According to a preferred embodiment of the present invention, in B2, the calcination time at 280-340°C is 2-3 hours.
[0020] In a second aspect, the present invention provides a high-temperature resistant, plugging-resistant, and anti-collapse drilling fluid treatment agent prepared according to the preparation method of the aforementioned high-temperature resistant, plugging-resistant, and anti-collapse drilling fluid treatment agent.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention utilizes a composite polymer network formed by 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, acrylamide, N-vinylpyrrolidone, dimethyl diallyl ammonium chloride, methyl allyl polyoxyethylene ether, and N,N'-methylenebisacrylamide to create a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent that also possesses the functions of saltwater resistance, adsorption and dispersion, coating and thickening, cation inhibition, and mild crosslinking enhancement. This polymer network maintains good chain segment extension and hydration film stability in a high-temperature brine environment, reducing the impact of thermal degradation and salting-out shrinkage on the treatment agent's performance, thereby improving the drilling fluid's rheological retention capacity, filtration control capacity, and cuttings coating capacity.
[0022] (2) After introducing titanium-silicon-aluminum intercalated vermiculite nanosheets, the present invention can utilize their layered structure to form spreading, bridging and supporting effects in wellbore pores and filter cake pores. Expanded vermiculite powder is acidified with hydrochloric acid aqueous solution, then dispersed with sodium hexametaphosphate, and forms a composite deposition structure with tetraisopropyl titanate, acetylacetone, tetraethyl orthosilicate and aluminum nitrate nonahydrate. After hydrothermal treatment and calcination, the resulting titanium-silicon-aluminum intercalated vermiculite nanosheets have good thermal stability, layer integrity and interfacial bonding ability, which can form a stable skeleton in drilling fluid filter cake, reducing the sealing failure caused by high temperature erosion and filter cake looseness.
[0023] (3) After introducing the phosphotungsten-cerium-zirconium-oxygen cluster plugging silicon ball in this invention, its spherical structure and surface oxygen cluster structure can be used to fill the small pores between the titanium-silicon-aluminum intercalated vermiculite nanosheets. The phosphotungsten-cerium-zirconium-oxygen cluster plugging silicon ball is made of tetraethyl orthosilicate, anhydrous ethanol, deionized water, ammonia, cerium nitrate hexahydrate, zirconium oxychloride octahydrate, phosphotungstic acid hydrate and acidic silica sol. It can form a tight plugging layer with the titanium-silicon-aluminum intercalated vermiculite nanosheets, which combines sheet-like bridging and spherical gap filling. After the vinyltrimethoxysilane is hydrolyzed by glacial acetic acid, it can enhance the combination between the inorganic components and the polymer network, so that a continuous, tough and erosion-resistant composite film layer is formed on the well wall surface, thereby reducing the intrusion of filtrate, inhibiting the hydration expansion and dispersion of shale, improving the stability of the well wall and reducing the risk of collapse. Detailed Implementation
[0024] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0025] Example 1: This example provides a method for preparing a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, the steps of which include: S1. Add 155.0g of deionized water to the reactor and stir at 25°C and 300r / min. Add 25.0g of 2-acrylamido-2-methylpropanesulfonic acid and 7.0g of acrylic acid, and stir until completely dissolved. Add sodium hydroxide to adjust the pH to 7.0, and control the system temperature during neutralization to not exceed 35°C to obtain a neutralized monomer solution. Add 36.5g of acrylamide, 10.5g of N-vinylpyrrolidone, 9.0g of dimethyl diallyl ammonium chloride, 4.0g of methyl allyl polyoxyethylene ether, and 0.11g of N,N'-methylenebis(methyl)acetal to the neutralized monomer solution. Acrylamide was mixed at 25°C and 400 rpm for 40 min to obtain a composite monomer solution. 3.25 g of vinyltrimethoxysilane was added to a mixture of 13.0 g of anhydrous ethanol and 11.5 g of deionized water, and the pH was adjusted to 4.5 with glacial acetic acid. The mixture was hydrolyzed at 25°C and 300 rpm for 30 min to obtain a silane hydrolysate. The silane hydrolysate was added to the composite monomer solution, along with 7.0 g of titanium-silicon-aluminum intercalated vermiculite nanosheets and 3.25 g of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres. The mixture was ultrasonically dispersed at 25°C for 30 min to obtain an inorganic composite monomer dispersion.
[0026] S2. The inorganic composite monomer dispersion was transferred into a reactor equipped with a stirrer and a nitrogen inlet device. The mixture was stirred at 300 r / min, and nitrogen was introduced for 30 min to remove oxygen from the system. The temperature was raised to 50°C under a nitrogen atmosphere, and 0.30 g of ammonium persulfate and 0.30 g of sodium bisulfite were added. The mixture was reacted at 50°C for 6.5 h to obtain a polymer gel. The polymer gel was cut into small pieces less than 5 mm, vacuum dried to constant weight at 77.5°C and a vacuum degree of -0.08 MPa, pulverized, and passed through a 150 μm sieve to obtain a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent.
[0027] Preparation steps of titanium-silicon-aluminum intercalated vermiculite nanosheets: A1. Add 25.0 g of expanded vermiculite powder to 220.0 g of 1.0 mol / L hydrochloric acid aqueous solution, stir at 70°C and 300 r / min for 4 h, filter, wash the obtained solid with deionized water until the pH of the final wash solution is 6.8, and then dry at 80°C for 12 h to obtain acidified vermiculite; add acidified vermiculite to 260.0 g of deionized water, add 3.5 g of sodium hexametaphosphate, stir at 25°C and 400 r / min for 30 min, and then ultrasonically disperse for 20 min to obtain acidified vermiculite dispersion; add 11.0 g of tetraisopropyl titanate... Ester, 8.0 g acetylacetone and 55.0 g anhydrous ethanol were mixed and stirred at 25°C and 300 r / min for 30 min to obtain a tetraisopropyl titanate complex solution. The tetraisopropyl titanate complex solution was added to an acidified vermiculite dispersion and stirred at 27.5°C and 400 r / min for 60 min. Then, 7.0 g tetraethyl orthosilicate and 6.0 g aluminum nitrate nonahydrate were added and stirred for another 30 min. Then, 25% ammonia water was added dropwise to adjust the pH to 8.85 and stirred at 50°C and 400 r / min for 3 h to obtain a titanium-silicon-aluminum intercalated vermiculite suspension.
[0028] A2. The titanium-silicon-aluminum intercalated vermiculite suspension was transferred into a polytetrafluoroethylene-lined reactor, sealed, and hydrothermally treated at 160°C for 10 h. After cooling to 25°C, the resulting system was centrifuged at 5000 r / min for 10 min. The obtained solid was washed three times with deionized water and once with anhydrous ethanol. It was then dried at 80°C for 12 h to obtain the hydrothermally treated product. The hydrothermally treated product was placed in a muffle furnace and calcined at 385°C for 3 h. After naturally cooling to 25°C, it was ground and passed through a 50 μm sieve to obtain titanium-silicon-aluminum intercalated vermiculite nanosheets.
[0029] Preparation steps of silicon spheres plugged with phosphotungsten-cerium-zirconium oxide clusters: B1. Add 8.0 g of tetraethyl orthosilicate to 100.0 g of anhydrous ethanol, stir at 25°C and 300 r / min for 10 min, add 27.5 g of deionized water and 4.5 g of ammonia, stir at 27.5°C and 400 r / min for 5 h to allow the tetraethyl orthosilicate to hydrolyze and condense. Then centrifuge at 5000 r / min for 10 min. Wash the obtained solid three times with deionized water to obtain a wet gel of nano-silica. The wet gel of nano-silica... The gel was added to 185.0 g of deionized water and stirred at 25°C and 400 r / min for 30 min. Then, 2.5 g of cerium nitrate hexahydrate, 1.75 g of zirconium oxychloride octahydrate and 4.0 g of phosphotungstic acid hydrate were added and stirred at 50°C and 400 r / min for 1.5 h. The pH was adjusted to 1.4 with nitric acid, and then 0.85 g of acidic silica sol was added. The mixture was aged at 85°C and 300 r / min for 5 h to obtain a suspension of phosphotungstic cerium zirconium oxide clusters blocking silica spheres.
[0030] B2. Filter the suspension of phosphotungsten-cerium-zirconium-oxygen cluster-sealed silicon spheres, wash the resulting solid three times with deionized water, and dry it at 80°C for 12 hours to obtain the dried product. Place the dried product in a muffle furnace and calcine it at 310°C for 2.5 hours. Allow it to cool naturally to 25°C, grind it, and pass it through a 25μm sieve to obtain phosphotungsten-cerium-zirconium-oxygen cluster-sealed silicon spheres.
[0031] Example 2: The difference between this example and Example 1 is that this example provides a method for preparing a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, the steps of which include: S1. Mix 120.0g deionized water, 18.0g 2-acrylamido-2-methylpropanesulfonic acid, and 4.0g acrylic acid. Adjust the pH to 6.8 with sodium hydroxide to obtain a neutralized monomer solution. Add 28.0g acrylamide, 6.0g N-vinylpyrrolidone, 5.0g dimethyl diallyl ammonium chloride, 2.0g methyl allyl polyoxyethylene ether, and 0.04g N,N'-methylenebisacrylamide to the neutralized monomer solution and continue... Mix for 40 min to obtain a composite monomer solution; add 1.5 g vinyltrimethoxysilane to a mixture of 8.0 g anhydrous ethanol and 8.0 g deionized water, adjust the pH to 4.0 with glacial acetic acid, and hydrolyze for 20 min to obtain a silane hydrolysate; add the silane hydrolysate to the composite monomer solution, add 4.0 g titanium-silicon-aluminum intercalated vermiculite nanosheets and 1.5 g phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres, and ultrasonically disperse for 20 min to obtain an inorganic composite monomer dispersion.
[0032] S2. Under a nitrogen atmosphere, the inorganic composite monomer dispersion was heated to 45°C, and 0.15g of ammonium persulfate and 0.15g of sodium bisulfite were added and reacted for 5 hours to obtain a polymer gel. The polymer gel was cut into small pieces, vacuum dried at 70°C to constant weight, pulverized, and sieved to obtain a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent.
[0033] Preparation steps of titanium-silicon-aluminum intercalated vermiculite nanosheets: A1. Add 20.0g of expanded vermiculite powder to 180.0g of hydrochloric acid aqueous solution, stir at 65°C for 4h, filter, wash with deionized water until the filtrate is nearly neutral, and dry at 80°C to constant weight to obtain acidified vermiculite; add acidified vermiculite to 220.0g of deionized water, add 2.0g of sodium hexametaphosphate, stir and disperse for 30min, then add a mixture of 8.0g tetraisopropyl titanate, 6.0g acetylacetone and 40.0g anhydrous ethanol, stir at 25°C for 60min, then add 5.0g tetraethyl orthosilicate and 4.0g aluminum nitrate nonahydrate, add ammonia to adjust the pH to 8.5, stir at 45°C for 2h to obtain titanium-silicon-aluminum intercalated vermiculite suspension.
[0034] A2. The titanium-silicon-aluminum intercalated vermiculite suspension was transferred into a reactor and hydrothermally treated at 150°C for 8 hours. After cooling to 25°C, it was centrifuged, and the resulting solid was washed three times with deionized water and dried at 80°C to constant weight to obtain the hydrothermally treated product. The hydrothermally treated product was calcined at 350°C for 2 hours, cooled to 25°C, ground, and sieved to obtain titanium-silicon-aluminum intercalated vermiculite nanosheets.
[0035] Preparation steps of silicon spheres plugged with phosphotungsten-cerium-zirconium oxide clusters: B1. Add 6.0g of tetraethyl orthosilicate to 80.0g of anhydrous ethanol, add 20.0g of deionized water and 3.0g of ammonia, stir at 25°C for 5h, centrifuge, and wash the resulting solid three times with deionized water to obtain nano-silica wet gel; disperse the nano-silica wet gel in 150.0g of deionized water, add 1.5g of cerium nitrate hexahydrate, 1.0g of zirconium oxychloride octahydrate and 2.5g of phosphotungstic acid hydrate, stir at 45°C for 1h, adjust the pH to 1.0, then add 0.5g of acidic silica sol, age at 80°C for 4h to obtain a suspension of phosphotungstic cerium zirconium oxide cluster-blocking silica spheres.
[0036] B2. Filter the suspension of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon balls, wash the resulting solid three times with deionized water, and dry it at 80°C to constant weight to obtain the dried product; calcine the dried product at 280°C for 2 hours, cool it to 25°C, grind it, and sieve it to obtain phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon balls.
[0037] Example 3: The difference between this example and Example 1 is that this example provides a method for preparing a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, the steps of which include: S1. Mix 190.0g deionized water, 32.0g 2-acrylamido-2-methylpropanesulfonic acid, and 10.0g acrylic acid. Adjust the pH to 7.2 with sodium hydroxide to obtain a neutralized monomer solution. Add 45.0g acrylamide, 15.0g N-vinylpyrrolidone, 13.0g dimethyl diallyl ammonium chloride, 6.0g methyl allyl polyoxyethylene ether, and 0.18g N,N'-methylenebisacrylamide to the neutralized monomer solution and continue... Mix for 40 min to obtain a composite monomer solution; add 5.0 g vinyltrimethoxysilane to a mixture of 18.0 g anhydrous ethanol and 15.0 g deionized water, adjust the pH to 5.0 with glacial acetic acid, and hydrolyze for 40 min to obtain a silane hydrolysate; add the silane hydrolysate to the composite monomer solution, add 10.0 g titanium-silicon-aluminum intercalated vermiculite nanosheets and 5.0 g phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres, and ultrasonically disperse for 40 min to obtain an inorganic composite monomer dispersion.
[0038] S2. Under a nitrogen atmosphere, the inorganic composite monomer dispersion was heated to 55°C, and 0.45g of ammonium persulfate and 0.45g of sodium bisulfite were added and reacted for 8 hours to obtain a polymer gel. The polymer gel was cut into pieces, vacuum dried at 85°C to constant weight, pulverized, and sieved to obtain a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent.
[0039] Preparation steps of titanium-silicon-aluminum intercalated vermiculite nanosheets: A1. Add 30.0g of expanded vermiculite powder to 260.0g of hydrochloric acid aqueous solution, stir at 75°C for 4h, filter, wash with deionized water until the filtrate is nearly neutral, and dry at 80°C to constant weight to obtain acidified vermiculite; add acidified vermiculite to 300.0g of deionized water, add 5.0g of sodium hexametaphosphate, stir and disperse for 30min, then add a mixture of 14.0g of tetraisopropyl titanate, 10.0g of acetylacetone and 70.0g of anhydrous ethanol, stir at 30°C for 60min, then add 9.0g of tetraethyl orthosilicate and 8.0g of aluminum nitrate nonahydrate, add ammonia water to adjust the pH to 9.2, stir at 55°C for 4h to obtain titanium-silicon-aluminum intercalated vermiculite suspension.
[0040] A2. The titanium-silicon-aluminum intercalated vermiculite suspension was transferred into a reactor and hydrothermally treated at 170°C for 12 hours. After cooling to 25°C, it was centrifuged, and the resulting solid was washed three times with deionized water and dried at 80°C to constant weight to obtain the hydrothermally treated product. The hydrothermally treated product was calcined at 420°C for 4 hours, cooled to 25°C, ground, and sieved to obtain titanium-silicon-aluminum intercalated vermiculite nanosheets.
[0041] Preparation steps of silicon spheres plugged with phosphotungsten-cerium-zirconium oxide clusters: B1. Add 10.0g of tetraethyl orthosilicate to 120.0g of anhydrous ethanol, add 35.0g of deionized water and 6.0g of ammonia, stir at 30°C for 5h, centrifuge, and wash the resulting solid three times with deionized water to obtain nano-silica wet gel; disperse the nano-silica wet gel in 220.0g of deionized water, add 3.5g of cerium nitrate hexahydrate, 2.5g of zirconium oxychloride octahydrate and 5.5g of phosphotungstic acid hydrate, stir at 55°C for 2h, adjust the pH to 1.8, then add 1.2g of acidic silica sol, age at 90°C for 6h to obtain a suspension of phosphotungstic cerium zirconium oxide cluster-blocking silica spheres.
[0042] B2. Filter the suspension of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon balls, wash the resulting solid three times with deionized water, and dry it at 80°C to constant weight to obtain the dried product; calcine the dried product at 340°C for 3 hours, cool it to 25°C, grind it, and sieve it to obtain phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon balls.
[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that 7.0g of titanium-silicon-aluminum intercalated vermiculite nanosheets are not added in step S1, while the rest is the same as in Example 1.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that 3.25g of phosphotungsten cerium zirconium oxide cluster sealing silicon balls are not added in step S1, while the rest is the same as in Example 1.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S1, the mixture of 3.25g vinyltrimethoxysilane, 13.0g anhydrous ethanol and 11.5g deionized water is not added, the pH is not adjusted to 4.5 with glacial acetic acid, hydrolysis is not performed for 30 minutes, and silane hydrolysate is not prepared. The rest is the same as in Example 1.
[0046] The performance of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agents obtained in Examples 1-3 and Comparative Examples 1-3 was tested.
[0047] The high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agents obtained in Examples 1-3 and Comparative Examples 1-3 were used as test samples. Drilling fluids were prepared for each sample. During preparation, 40.0g of sodium-based bentonite and 3.0g of anhydrous sodium carbonate were added to 1000.0g of deionized water. The mixture was stirred at 25°C for 30 minutes and then sealed for 24 hours to obtain a pre-hydrated base slurry. 30.0g of sodium chloride and 15.0g of calcium chloride were added to the pre-hydrated base slurry, and the mixture was stirred at 25°C for 30 minutes to obtain a high-salt base slurry. Add 15.0g of the test samples obtained in Examples 1, 2, 3, 1, 2, or 3 respectively to the high-salt slurry, and stir at 25°C for 40min to obtain the corresponding drilling fluid to be tested; put the drilling fluid to be tested into high-temperature aging tanks, the liquid volume of which is 70% of the effective volume of the aging tank, seal them and place them in a roller heating furnace, and roll and age them at 180°C for 16h. After taking them out, let them cool naturally to 25°C, and then stir them at high speed for 10min before testing.
[0048] During the apparent viscosity retention rate test, the drilling fluid to be tested before and after aging was taken separately, and the apparent viscosity was measured at 25°C using a rotational viscometer. The apparent viscosity retention rate was calculated as apparent viscosity after aging ÷ apparent viscosity before aging × 100%.
[0049] During the high-temperature and high-pressure filtration loss test, the aged drilling fluid to be tested is poured into the slurry cup of the high-temperature and high-pressure filtration loss instrument, filter paper is added and sealed, and the test is conducted for 30 minutes at 180°C and 3.5MPa. The filtrate is collected and the filtrate volume is read. The obtained filtrate volume is recorded as the high-temperature and high-pressure filtration loss.
[0050] During the filter cake thickness test, after the high temperature and high pressure filtration loss test, remove the filter paper and filter cake, gently wash the surface slurry of the filter cake with a small amount of deionized water, keep the filter cake intact, and use vernier calipers to evenly select 5 positions at the center and periphery of the filter cake to measure the thickness, and take the average value as the filter cake thickness.
[0051] During the sealing pressure resistance test, the aged drilling fluid to be tested was added to a sealing evaluation device equipped with a micro-fracture simulation sand disc. The pressure was increased from 1.0 MPa at 25°C, with each increase being 0.5 MPa. Each pressure level was maintained for 5 minutes. The highest pressure when there was no continuous sudden increase in filtrate, sudden drop in pressure, or obvious loss of sealing was recorded as the sealing pressure resistance.
[0052] For the shale rolling recovery rate test, 50.0g of dry shale cuttings with a particle size of 2.0-5.0mm were weighed and added to 350.0mL of aged drilling fluid to be tested. After sealing, the mixture was rolled at 120°C for 16h. After cooling to 25°C, the cuttings were recovered using a 0.425mm sieve. The surface mud adhering to the cuttings was quickly rinsed with deionized water. The mixture was dried at 105°C for 4h and weighed. The shale rolling recovery rate was calculated as the weight of recovered dry cuttings ÷ the initial weight of dry cuttings × 100%.
[0053] During the linear expansion rate test, bentonite was pressed into core pieces with a diameter of 25.0 mm and a thickness of 10.0 mm, placed in the test cylinder of the linear expansion instrument, and aged drilling fluid to be tested was added. The test was conducted continuously at 25°C for 16 hours, and the increase in core piece thickness was recorded. The linear expansion rate was calculated as the increase in thickness ÷ initial thickness × 100%. All six tests were performed in parallel for each sample, and the average value of the results was taken.
[0054] The performance test data above are shown in Table 1.
[0055] Table 1: Performance Test Results
[0056] The test results in Table 1 clearly show that Examples 1-3 significantly improved upon Comparative Examples 1-3 the problems of viscosity decay, increased filtration loss, loose filter cake, insufficient sealing pressure, and shale hydration dispersion of existing high-temperature resistant plugging and anti-collapse drilling fluid treatment agents in high-temperature brine environments compared to Comparative Examples 1-3.
[0057] After rolling aging at 180°C for 16 hours, the apparent viscosity retention rate of Examples 1-3 still reached 88.5%-91.8%, which was significantly higher than that of Comparative Example 1 (77.2%), Comparative Example 2 (80.5%), and Comparative Example 3 (73.6%). This indicates that the synergistic effect of titanium-silicon-aluminum intercalated vermiculite nanosheets, phosphotungsten-cerium-zirconium oxide cluster-blocked silicon spheres, and vinyltrimethoxysilane can improve the structural stability of the polymer network in a high-temperature salt water environment and reduce the chain segment degradation, inorganic component aggregation, and viscosity loss caused by high-temperature aging.
[0058] The high-temperature and high-pressure filtration loss of Examples 1-3 was 8.6-10.1 mL, which was significantly lower than that of Comparative Example 1 (18.9 mL), Comparative Example 2 (16.4 mL), and Comparative Example 3 (21.7 mL). Furthermore, the filter cake thickness of Examples 1-3 was only 0.8-1.0 mm, which was lower than that of Comparative Example 1 (1.8 mm), Comparative Example 2 (1.5 mm), and Comparative Example 3 (2.1 mm). This indicates that Examples 1-3 can form thinner and denser filter cakes, effectively reducing the intrusion of filtrate into formation pores and microfractures.
[0059] Further examining the sealing pressure resistance, Examples 1-3 achieved 6.1-6.8 MPa, while Comparative Examples 1-3 only achieved 3.5-4.4 MPa. This indicates that the titanium-silicon-aluminum intercalated vermiculite nanosheets can play a role in sheet-like bridging and skeletal support, the phosphorus-tungsten-cerium-zirconium-oxygen cluster sealing silicon spheres can play a role in spherical interstitial filling and micro / nanopore sealing, and the vinyltrimethoxysilane enhances the bonding strength between the two inorganic components and the polymer network.
[0060] When Comparative Example 1 lacked titanium-silicon-aluminum intercalated vermiculite nanosheets, the filtration loss increased to 18.9 mL, the filter cake thickness increased to 1.8 mm, and the sealing pressure resistance decreased to 3.9 MPa, indicating that it is difficult to establish a stable sheet-like bridging sealing framework by relying solely on phosphorus-tungsten-cerium-zirconium-oxygen clusters to seal silicon spheres.
[0061] When Comparative Example 2 lacked phosphotungsten-cerium-zirconium-oxygen clusters to plug the silicon spheres, the filtration loss was 16.4 mL, the filter cake thickness was 1.5 mm, and the plugging pressure resistance was 4.4 MPa. This indicates that although only titanium-silicon-aluminum intercalated vermiculite nanosheets can provide a certain bridging effect, they are insufficient to fill the fine pores and interlayer gaps.
[0062] When comparative example 3 lacked vinyltrimethoxysilane, the apparent viscosity retention rate was the lowest, at only 73.6%, the high temperature and high pressure filtration loss was the highest, reaching 21.7 mL, and the sealing pressure resistance was the lowest, at only 3.5 MPa. This indicates that the lack of effective connection between the inorganic components and the polymer network leads to a decrease in the stability of the composite sealing structure under high temperature shear and salt water conditions.
[0063] The shale rolling recovery rate of Examples 1-3 reached 91.9-94.7%, which was significantly higher than that of Comparative Example 1 (83.6%), Comparative Example 2 (86.2%), and Comparative Example 3 (80.4%). At the same time, the linear expansion rate was reduced to 13.2-15.4%, which was significantly lower than that of Comparative Example 1 (21.7%), Comparative Example 2 (19.8%), and Comparative Example 3 (24.3%). This indicates that Examples 1-3 can not only reduce filtrate intrusion, but also inhibit the hydration expansion and dispersion spalling of mudstone and shale through polymer coating, cationic adsorption, sheet-like covering, and spherical interstitial filling.
[0064] In summary, Examples 1-3, through the synergistic effect of titanium-silicon-aluminum intercalated vermiculite nanosheets, phosphorus-tungsten-cerium-zirconium-oxygen clusters sealing silicon spheres, and vinyltrimethoxysilane, solved the technical problems of insufficient temperature resistance stability, non-dense sealing layer, weak filtration control, poor shale suppression effect, and insufficient wellbore anti-collapse ability of existing drilling fluid treatment agents under high-temperature brine conditions.
Claims
1. A method for preparing a high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, characterized in that the steps include... include: S1. Deionized water, 2-acrylamido-2-methylpropanesulfonic acid, and acrylic acid are mixed, and sodium hydroxide is added to adjust the pH to 6.8-7.2 to obtain a neutralized monomer solution. Acrylamide, N-vinylpyrrolidone, dimethyl diallyl ammonium chloride, methyl allyl polyoxyethylene ether, and N,N'-methylenebisacrylamide are added to the neutralized monomer solution, and mixing is continued to obtain a composite monomer solution. Vinyltrimethoxysilane is added to a mixture of anhydrous ethanol and deionized water, and the pH is adjusted to 4.0-5.0 with glacial acetic acid. Hydrolysis is performed to obtain a silane hydrolysate. The silane hydrolysate is added to the composite monomer solution, and titanium-silicon-aluminum intercalated vermiculite nanosheets and phosphotungsten-cerium-zirconium oxygen clusters are added to block silicon spheres. The mixture is then ultrasonically dispersed to obtain an inorganic composite monomer dispersion. S2. Under a nitrogen atmosphere, the inorganic composite monomer dispersion is heated to 45-55℃, and ammonium persulfate and sodium bisulfite are added to react and obtain polymer gel; the polymer gel is cut into pieces, vacuum dried, pulverized and sieved.
2. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 1, characterized in that, In S1, the amounts of deionized water, 2-acrylamido-2-methylpropanesulfonic acid, and acrylic acid in the neutralizing monomer solution are 120.0-190.0 parts, 18.0-32.0 parts, and 4.0-10.0 parts, respectively, by weight. In the composite monomer solution, the amounts of acrylamide, N-vinylpyrrolidone, dimethyl diallyl ammonium chloride, methyl allyl polyoxyethylene ether, and N,N'-methylenebisacrylamide are 28.0-45.0 parts, 6.0-15.0 parts, 5.0-13.0 parts, 2.0-6.0 parts, and 0.04-0.18 parts, respectively. In the silane hydrolysate, the amounts of vinyltrimethoxysilane, anhydrous ethanol, and deionized water are 1.5-5.0 parts, 8.0-18.0 parts, and 8.0-15.0 parts, respectively. In the inorganic composite monomer dispersion, the amounts of titanium-silicon-aluminum intercalated vermiculite nanosheets and phosphorus-tungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres are 4.0-10.0 parts and 1.5-5.0 parts, respectively; the hydrolysis time is 20-40 min; and the ultrasonic dispersion time is 20-40 min.
3. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 1, characterized in that, In step S2, the amounts of ammonium persulfate and sodium bisulfite, by weight, are 0.15-0.45 parts and 0.15-0.45 parts, respectively; the reaction time is 5-8 hours; and the vacuum drying temperature is 70-85°C.
4. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 1, characterized in that, The preparation method of the titanium-silicon-aluminum intercalated vermiculite nanosheets includes: A1. By weight, add 20.0-30.0 parts of expanded vermiculite powder to 180.0-260.0 parts of a 1.0 mol / L hydrochloric acid aqueous solution, stir at 65-75℃, filter, wash, and dry to obtain acidified vermiculite; add the acidified vermiculite to 220.0-300.0 parts of deionized water, add 2.0-5.0 parts of sodium hexametaphosphate, disperse, then add a mixture containing 8.0-14.0 parts of tetraisopropyl titanate, 6.0-10.0 parts of acetylacetone and 40.0-70.0 parts of anhydrous ethanol, stir at 25-30℃, then add 5.0-9.0 parts of tetraethyl orthosilicate and 4.0-8.0 parts of aluminum nitrate nonahydrate, add ammonia to adjust the pH to 8.5-9.2, stir at 45-55℃ to obtain a titanium-silicon-aluminum intercalated vermiculite suspension; A2. The titanium-silicon-aluminum intercalated vermiculite suspension is transferred into a reactor and hydrothermally treated at 150-170℃. After cooling, centrifugation, washing, and drying, the hydrothermally treated product is obtained. The hydrothermally treated product is calcined at 350-420℃, ground, and sieved.
5. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 4, characterized in that, In A1, the stirring time is 2-4 hours at 45-55℃.
6. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 4, characterized in that, In A2, the hydrothermal treatment time at 150-170℃ is 8-12 hours; the calcination time at 350-420℃ is 2-4 hours.
7. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 1, characterized in that, The method for preparing the phosphotungsten-cerium-zirconium-oxygen cluster-sealed silicon spheres includes: B1. By weight, add 6.0-10.0 parts of tetraethyl orthosilicate to 80.0-120.0 parts of anhydrous ethanol, add 20.0-35.0 parts of deionized water and 3.0-6.0 parts of ammonia water, stir at 25-30℃, centrifuge, and wash to obtain a nano-silica wet gel; disperse the nano-silica wet gel in 150.0-220.0 parts of deionized water, add 1.5-3.5 parts of cerium nitrate hexahydrate, 1.0-2.5 parts of zirconium oxychloride octahydrate and 2.5-5.5 parts of phosphotungstic acid hydrate, stir at 45-55℃, adjust the pH to 1.0-1.8, then add 0.5-1.2 parts of acidic silica sol, age at 80-90℃ to obtain a phosphotungstic cerium zirconium oxide cluster blocking silica ball suspension; B2. Filter, wash, and dry the suspension of phosphotungsten-cerium-zirconium-oxygen cluster-blocked silicon spheres to obtain a dried product; calcine the dried product at 280-340℃, grind, and sieve.
8. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 7, characterized in that, In B1, the stirring time at 45-55℃ is 1-2 hours; the aging time at 80-90℃ is 4-6 hours.
9. The preparation method of the high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent according to claim 7, characterized in that, In the B2, the calcination time at 280-340℃ is 2-3 hours.
10. A high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent, characterized in that, The high-temperature resistant, plugging, and anti-collapse drilling fluid treatment agent is prepared according to the preparation method of any one of claims 1-9.